Architectural Object on an Archaeological Site: The Transformation of an Image during the Restoration Process - Kazaryan, Armen Yu. (Actual Problems of Theory and History of Art, 2017)
The article analyzes the changes of an image of the monuments of ancient and medieval architecture during conservation or restoration works. Special attention has been paid to the recent condition of the town of Ani (Turkey), the medieval Armenian capital abandoned ages ago. It has been concluded that not only the restoration but sometimes even the conservation of a monument could change its image. Obviously, each case of restoration works needs a philosophical conception in terms of whole town or ensemble. We need a strategy for the protection of Ani, where dozens of ruins and fragments of constructions still remain. This strategy cannot proceed from international legal documents only.
Keywords: monument; architecture; ruin; image; Ani; preservation; conservation